Causality between Exchange Rate and Foreign Exchange Reserves in the Indian Context (Global Journal of Management and Business Research, 2013)
Using a time series data of the variables between 1980 and 2010 the present study tries to establish a causal relationship between exchange rate and foreign exchange reserves in the Indian context. Emphasis has been laid on understanding the impact of foreign exchange reserves on the exchange rate. India has accumulated unprecedented foreign exchange reserves and synchronously has been experiencing a large depreciation in its Rupee vies avis US dollar. This trend prompted us to undertake this study to establish some association between the two trends. Our analysis uses Unit Root test, Johansson Co-integration test and Vector Auto Regression (VAR) and concludes that there is no long and short term association between exchange rate (EXR) and foreign exchange reserves (FOREX) in the Indian context.
Keywords: foreign exchange reserves; exchange rate; fore; ear; vector auto regression (vary) appreciation and depreciation of currency money supply